Natural fibre sourcing for textile architecture - Ilaria Pugliese; Samica Sadik; Alessandra Zanelli (Techne)
Local resources can provide industrial production opportunities to improve processes while enhancing biodiversity and the use of raw materials. This research profiles currently underused bast plant fibres for environmentally sound textile applications in architecture – a sector heavily reliant on non-renewable resources – by comparing their technical properties and environmental impacts to support material selection. It also reconstructs production scenarios by evaluating fibre material typologies, their processability in textile-based building materials, and the existing fibre processing and textile manufacturing infrastructure.